Daily exchange rate pass-through into micro prices. Issue 6 (30th March 2019) - Alvarez, Renzo; Shoja, Amin; Uddin, Syed; Yilmazkuday, Hakan
ABSTRACT: This article estimates the exchange rate pass-through (ERPT) by using good-level daily data on wholesale prices of imported agricultural products, where the identification is achieved by using daily data on the domestic inflation rate. The results of standard empirical analyses are in line with existing studies that employ lower frequencies of data by showing evidence for incomplete daily ERPT of about5 %. The key innovation is achieved when nonlinearities in ERPT are considered, where ERPT is doubled to about10 % when daily nominal exchange rate changes are above0.55 %, daily frequencies of price change are above3.12 % and storage life of a product is above10 weeks. Important policy implications follow.